Communities of Practice in Graduate Education: The Learner's Perspective - Catherine H. Monoghan (Adult Education Research Conference, 2007)
The focus of this paper is the use of Communities of Practice as a tool to help learners acquire lifelong learning skills. The purpose of this research was to assess the effectiveness of this learning strategy to better understand how educators can help students to become lifelong learners.